Two vs three cycles of neoadjuvant immunochemotherapy for resectable non-small-cell lung cancer: a real-world population-based study - Xiu, Jiawei; Yao, Xin; Sun, Ying; Xu, Shaopeng; Wang, Chao; Duan, Hongtao; Yan, Xiaolong (Frontiers in Immunology, 2025)
ObjectiveInvestigation of the Impact of Neoadjuvant Immunochemotherapy Cycles on Pathological Response, Perioperative Safety, and Survival Outcomes in Patients with Resectable Non-Small Cell Lung Cancer (NSCLC).MethodsThis study utilized real-world data, focusing on patients with stage IIA-IIIB non-small cell lung cancer (NSCLC) who underwent neoadjuvant immunochemotherapy followed by surgical resection. Subjects were stratified into groups based on whether they received two or three cycles of neoadjuvant therapy. Propensity score matching (PSM) and inverse probability weighting (IPW) analyses were utilized to adjust for covariates, thereby balancing seven clinically relevant variables, including demographic factors, and tumor characteristics, to ensure baseline comparability. Following the application of PSM and IPW, comparisons were conducted between the two-cycle and three-cycle groups in terms of pathological response indicators [pathological complete response (pCR) and major pathological remission (MPR)], perioperative safety metrics, and survival outcomes [overall survival (OS) and disease-free survival (DFS)].ResultspCR rates were comparable between the three-cycle and two-cycle groups both before adjustment (40.2% vs 42.0%; OR = 0.93, P = 0.777) and after PSM (48.1% vs 42.0%; OR = 1.28, P = 0.430) or IPW (42.0% vs 43.7%; OR = 0.93, P = 0.801). Similarly, MPR rates showed no significant differences (pre-adjustment: 63.8% vs 70.4%, P = 0.283; PSM: 66.7% vs 70.4%, P = 0.612; IPW: 64.6% vs 69.5%, P = 0.440). Perioperative safety profiles were comparable. After median follow-ups of 25.3 (three-cycle) and 31.3 (two-cycle) months, three-year DFS (84.6% vs 88.2%; HR = 1.04, P = 0.921) and OS (88.6% vs 88.2%; HR = 0.94, P = 0.892) were not significantly different. Achieving MPR or pCR was independently associated with significantly improved DFS (MPR: HR = 0.25, P < 0.001; pCR: HR = 0.25, P = 0.005) and OS (MPR: HR = 0.30, P = 0.002; pCR: HR = 0.28, P = 0.018) compared to non-responders.ConclusionOur analysis demonstrated comparable pathological responses (pCR/MPR) between 2-cycle and 3-cycle neoadjuvant immunochemotherapy.